UPAYA MENINGKATKAN KREATIVITAS ANAK USIA DINI MELALUI MEDIA BERMAIN BALOK DI TAMAN KANAK-KANAK BAITUL ILMI PADANG SERAI BENGKULU - Susanti, Fenty; Nurhafizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to improve early childhood creativity through block play media at Baitul Ilmi Kindergarten, Padang Serai, Bengkulu City. The study employed Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The research subjects were 15 children in Group B. Data were collected through observation, documentation, and assessment of children's work. The results indicated that the use of block play media effectively improved children's creativity. In Cycle I, children who achieved the categories of Developing as Expected (DAE) and Very Well Developed (VWD) reached 26.67%, while in Cycle II the percentage increased to 80.00%. The children demonstrated better abilities in expressing ideas, using imagination, creating various building forms, and completing tasks independently. Therefore, block play media proved to be effective in enhancing early childhood creativity at Baitul Ilmi Kindergarten, Padang Serai, Bengkulu City. Keywords: Creativity, Early Childhood Education, Block Play, Learning Media, Classroom Action Research.